Pemberdayaan masyarakat melalui KKN-PPM untuk meningkatkan kualitas hidup masyarakat DAS Sungai Walanae Kabupaten Wajo - Marsud Hamid (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Tadampalie Village is one of the villages inSabbangparu Subdistrict which is in direct contact with thepotential Walanae River with fish yield. But the problemsfaced are: 1) the lack of technology carried out by thecommunity in processing and utilizing the existing localpotential, 2) the limitations in getting clean water, 3) theenvironment which is often flooded. Based on this basis, theKKN-PPM was agreed to be implemented in 2018. The mainprogram is processing fish into ready-to-eat food, smoked fishprocessing, and the application of appropriate technology forwater purification systems and utilization of environmentalorientedseptic tanks. it is expected that the quality of life andincome of the community will increase. The methods used aretraining, mentoring, lectures, practices and demonstrations.This KKN-PPM activity also involves partner institutions, theWajo Regional Government and community leaders inSabbangparu District. The number of students involved is 30 people with varied disciplines. The outputs are (1) theexistence of processed fish products such as: nuget, and abonikan, (2) smoked fish, (3) technology tools for fish fumigation,and (4) availability of simple water purification systems foreach citizen and (5) model of septic tank Environmentalinsight. Thus, it is expected that the quality of life of thepeople in Tadampalie Village can increase, includingcommunity income.